Strategi Bertahan Hidup Petani Berbasis Aset Pasca Pembangunan PLTU Karangkandri di Desa Slarang Kabupaten Cilacap (Laboratorium Sosiologi FISIP Universitas Jember, 2023)
This research started with the researcher's interest in the impact of the Karangkandri Power plant on the productivity of farmers in Slarang Village, Kesugihan District, Cilacap Regency. This qualitative research using the case study method aims to analyze the condition of livelihood assets and farmers' survival strategies after the construction of PLTU Karangkandri. The researcher used the theory from the Department for International Development (DFID) regarding Pentagon Assets and the theory of Survival Strategy (Strategic Coping) by Edi Suharto to investigate farmers'survival strategies after the construction of Power plant. The results of the study show that the livelihood assets owned by farmers in survival consist of natural capital, human capital, physical capital, financial capital and social capital. Meanwhile, natural capital and social capital are the main capital used by farmers in meeting the needs of life and demanding a decent living for PT Sumber Segara Primadaya (S2P). The survival effort is divided into three strategies, namely active, passive and network strategies. The active strategy consists of diversifying jobs, participating in skills training, and adding manpower. Passive strategy is minimizing spending on basic needs and agricultural production. The network strategy is utilizing social networks to meet urgent needs and demand a decent living for PT Sumber Segara Primadaya (S2P). Keywords: Coping Strategies, Pentagon Assets, farmer, PLTU